1993
DOI: 10.1042/bj2920705
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a cDNA encoding bovine mitochondrial NADP+-specific isocitrate dehydrogenase and structural comparison with its isoenzymes from different species

Abstract: Mitochondrial NADP(+)-specific isocitrate dehydrogenase (IDP) was co-purified with the pyruvate dehydrogenase complex from bovine kidney mitochondria. The determination of its N-terminal 16-amino-acid sequence revealed that it is highly similar to the IDP from yeast. A cDNA clone (1.8 kb long) encoding this protein was isolated from a bovine kidney lambda gt11 cDNA library using a synthetic oligodeoxynucleotide. The deduced protein sequence of this cDNA clone rendered a precursor protein of 452 amino-acid resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
(39 reference statements)
1
32
0
Order By: Relevance
“…The icdk-2 cDNA had a length of 1569 bp and was predicted to encode a polypeptide of 416 amino acids, corresponding to about 45.5 kD. This finding fits well with determinations from other authors (Haselbeck and McAlister-Henn, 1991: yeast, 45 kD;Shorrosh and Dixon, 1992: alfalfa, 46 kD;Huh et al, 1993: bovine kidney, 46 kD). The 3' untranslated region of the cDNA includes the polyadenylation signal AATAAA (position 1378-1383).…”
Section: The Deduced Protein Sequence Of Icdh-1 From Potato Shows Sigsupporting
confidence: 80%
See 1 more Smart Citation
“…The icdk-2 cDNA had a length of 1569 bp and was predicted to encode a polypeptide of 416 amino acids, corresponding to about 45.5 kD. This finding fits well with determinations from other authors (Haselbeck and McAlister-Henn, 1991: yeast, 45 kD;Shorrosh and Dixon, 1992: alfalfa, 46 kD;Huh et al, 1993: bovine kidney, 46 kD). The 3' untranslated region of the cDNA includes the polyadenylation signal AATAAA (position 1378-1383).…”
Section: The Deduced Protein Sequence Of Icdh-1 From Potato Shows Sigsupporting
confidence: 80%
“…The overall sequence identity amounts to about 97% for tobacco (S. Gálvez, EMBL Data Library, accession No. X77944), to 90% for soybean (Udvardi et al, 1993) and alfalfa (Shorrosh and Dixon, 1992), to more than 65% for cattle (Huh et al, 1993), pig (Haselbeck et al, 1992), and yeast (Haselbeck and McAlister-Henn, 1991), and finally to 25% for Escherickiu coli (Thorsness and Koshland, 1987). Southern blot analysis of digested genomic DNA from potato probed with the complete icdh-2 cDNA fragment showed only a few bands (Fig.…”
Section: The Deduced Protein Sequence Of Icdh-1 From Potato Shows Sigmentioning
confidence: 99%
“…Isocitrate NADP 2H Both isozymes have been purified from several mammals and their cDNA sequences were determined (Plaut et al 1983;Haselbeck et al 1992;Huh et al 1993;Jennings et al 1994;Loftus et al 1994;Yang et al 1996;Nekrutenko et al 1998). ICD1 and ICD2 are homodimers encoded in the nuclear genome (Loftus et al 1994).…”
mentioning
confidence: 99%
“…Experiments using antibody-absorbing PVDF membranes showed that the anti-ICD1 peptide antibody could react with ICD1 to reduce the enzymatic activity in heart extract. Furthermore, Western blotting analysis showed that the anti-peptide antibody reacted with a single protein band with a molecular mass of 45 kD, which was considerably smaller than the unprocessed precursor form that had been predicted from DNA sequences so far: bovine, 50,824 (Huh et al 1993); human, 50,948 (Huh et al 1993); mouse, 58,749 (Yang et al 1996);pig, 47,526 (Haselbeck et al 1992); and yeast, 48,009 (Imajo et al 1997). These precursor forms of ICD1 seem to be imported into mitochondria and the signal sequence is cut off to form the mature enzyme.…”
Section: Specificity Of Antibodymentioning
confidence: 99%
“…Both enzymes have been purified from various sources and their cDNA sequences determined (Macfarlane et al 1977;Haselbeck et al 1992;Huh et al 1993;Jennings et al 1994;Loftus et al 1994;Yang et al 1996;Nekrutenko et al 1998). ICD1 and ICD2 are homodimers encoded in the nuclear genome (Loftus et al 1994).…”
mentioning
confidence: 99%